Guillain-Barré syndrome, about a disease that is a challenge for doctors of various specialties - Musiał, Natalia; Jankowicz-Szymańska, Agnieszka; Pietrzyk, Jacek (Health Promotion & Physical Activity, 2018)
Although the Guillain-Barré syndrome is relatively rare, it is a disease entity that doctors of different specialties and physiotherapists should know as much as possible. This is a post-infectious autoimmune polyneuropathy. This condition falls on the patient unexpectedly and in a short time can lead to damage to many organs and even life-threatening. Due to the multitude and variety of symptoms, treatment of the Guillain-Barré syndrome, more than other diseases, requires close cooperation of the entire therapeutic team. A physiotherapist plays a special role in working with a patient with the Guillain-Barré syndrome. Restoration of lost or limited functions requires time, patience, knowledge and experience to select the methods of working with the patient in the most effective way.